Pengembangan Media Explosion Box Berbasis Pendekatan PBL untuk Meningkatkan Pemahaman Mitigasi Gempa - Rivana Al Ghanisa; Sandi Budi Iriawan; Mela Darmayanti (SAP (Susunan Artikel Pendidikan), 2025)
This study used the D&D method proposed by Richey and Klein, whereby the media development process included the stages of needs analysis, design, prototype development, implementation, and evaluation. Validation was carried out by three validators, namely subject matter experts, media experts, and learning experts. The validation results showed that the media was very suitable for use, with validation scores of 92.5% (material), 92.86% (media), and 95.56% (learning). A limited trial was conducted with 18 fifth-grade students and showed an increase in their understanding of earthquake mitigation. The students' average score increased from 54.97% on the pre-test to 84.59 on the post-test. The use of the Explosion Box media not only made learning more interesting, but also helped students understand earthquake mitigation material in a contextual and in-depth manner. Earthquake mitigation learning is very important for elementary school students, especially in earthquake-prone areas, so that students can improve their preparedness when an earthquake occurs.